IMPROVING EMPLOYEE PERFORMANCE THROUGH WORK SPIRIT AND WORK CULTURE OF EMPLOYEES IN THE DISTRICT ENVIRONMENT OF CILEGON CITY, BANTEN PROVINCE - Raditha, Amanda; Khaeruman, Khaeruman; Susanto, Budi (Yayasan Education and Social Center, 2024)
Management is a function that is concerned with realizing certain results through the activities of people. Human Resources are one of the people employed in an organization as a driving force to achieve the organization's goals. This research aims to analyze performance improvement through work enthusiasm, performance improvement through work culture and performance improvement through work spirit and work culture simultaneously in the Cilegon City District Environment, Banten Province. This research uses quantitative research methods to analyze the relationship between work morale, work culture, and employee performance. The research population includes all Civil Servants in the District of Cilegon City, Banten Province with a sample of 61 respondents. Results of the t test on employee performance through work enthusiasm, namely the t valuecount > ttable (24.407 > 1.673), t-test results of employee performance through work culture, namely the t valuecount > ttable (20.922 > 1.673) and the results of the F test of employee performance through work enthusiasm and work culture simultaneously are Fcount > Ftable (2.378> 2.53). This research concludes that there is a significant increase in employee performance through work morale and a significant increase in employee performance through work culture, and there is a significant increase in employee performance through work morale and work culture simultaneously with a coefficient of determination of 98.8%. while the remaining 1.2% is influenced by other variables not explained in this research model